Elevated Levels of Soluble Axl (sAxl) Regulates Key Angiogenic Molecules to Induce Placental Endothelial Dysfunction and a Preeclampsia-Like Phenotype - Gui, Shunping; Zhou, Shengping; Liu, Min; Zhang, Yanping; Gao, Linbo; Wang, Tao; Zhou, Rong (Frontiers in Physiology, 2021)
Preeclampsia is a severe pregnancy-specific syndrome characterized by impaired placental angiogenesis. Although its pathogenesis remains largely unclear, vascular systemic endothelial injury is thought to be the central link that contributes to the development of preeclampsia. Soluble Axl (sAxl), a biomarker of endothelial dysfunction, was observed to an abnormal increase in various diseases associated with vascular injury. Our previous study has found that plasma sAxl was significantly higher in preeclampsia patients than normal pregnant women, this study aims to further explore the potential role of sAxl in the development of vascular injury in preeclampsia. We found the upregulation of sAxl in plasma had a positive correlation with plasma sFlt-1 and a negative correlation with placental NO synthase (eNOS) in preeclampsia women. In addition, elevated sAxl suppressed proliferation and tube formation, and promoted cytotoxicity of human umbilical vein endothelial cells (HUVECs) by down-regulate the expression of p-Akt, p-p70S6K, p-mTOR and Grb2. Then, we established a rat model with preeclampsia-like characteristics using the adenovirus expressing sAxl by tail vein injection. sAxl-treated rat exhibited classic preeclampsia-like phenotype: increased blood pressure, proteinuria, fetal growth restriction, abnormal placental and renal morphology. In conclusion, our study shows the role of sAxl in systemic vascular injury by differentially regulating the expression of key molecules of angiogenesis, potentially contributing to the development of preeclampsia.